Analysis of the Effect of Perceived Product Quality on Retail Purchase Intention: The Mediating Role of Consumer Trust and Price Sensitivity Moderation - Yoga Religia; Yussi Ramawati; Muhamad Syahwildan (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2024)
Small informal retailers play a crucial role in the local economy, with consumer purchase intentions being the backbone of their sustainability. The purpose of this research is to explore the relationship between perceived product quality, consumer trust, and price sensitivity to purchase intention among small retailers. This research data was obtained from Mendeley data in the form of subsistence retail consumer data consisting of 281 respondents. The analysis was carried out using SmartPLS because it can be used as a measuring tool in SEM analysis more easily, quickly and efficiently. The test results show that perceived product quality has a significant positive effect on purchase intention. Positively perceived product quality makes a strong impression on consumers, increasing their trust in the retailer. However, low consumer confidence in retailers can result in decreased purchase intentions due to uncertainty and doubts about the quality of the products or services offered. In addition, price sensitivity also moderates the relationship between perceived product quality and purchase intention. This research provides insight into the interrelationships between perceived product quality, consumer trust, price sensitivity, and purchase intention in the context of informal small retailers, which can enrich marketing theories related to consumer behavior and purchasing decisions.